Sheehan’s syndrome with delayed diagnosis - Nagabhushanarao, Bhavana V.; Kalidindi, Ravikumar V.; Sundarpal, Prasadarao; Kimidi , Ruchirapriya (International Journal of Research in Medical Sciences, 2025)
Sheehan’s syndrome is a rare but important cause of hypopituitarism, typically resulting from ischemic necrosis of the anterior pituitary gland following severe postpartum hemorrhage. Its presentation may be acute or delayed, often leading to diagnostic challenges, particularly in regions with limited obstetric facilities. This case reports the case of a 57-year-old woman who presented with chronic fatigue, dizziness, and hypotension. She had a history of severe postpartum hemorrhage decades earlier, followed by failure of lactation and amenorrhea. Evaluation revealed secondary hypothyroidism and adrenal insufficiency. Magnetic resonance imaging (MRI) brain demonstrated an atrophied pituitary with a thin rim of residual tissue. She was diagnosed with Sheehan’s syndrome and treated with hydrocortisone replacement, followed by levothyroxine titrated according to free T4 levels. At six-month follow-up, she was asymptomatic with complete resolution of clinical features. This case highlights the importance of considering Sheehan’s syndrome in women with unexplained hypothyroidism, hypotension, or amenorrhea with a history of postpartum hemorrhage. Cortisol replacement must always precede thyroid hormone therapy to avoid adrenal crisis. Early recognition and appropriate hormone replacement therapy ensure favorable long-term outcomes.